Iraq old land, new nation in conflict - Spencer, William (Brookfield, Conn. : Twenty-First Century Books, 2000)
Traces the history of Iraq, from its Mesopotamian origins to its current political turbulence and its crises with international relations.
includes bibliographical references and index
12 - 15 years
Keywords: Iraq -- History